2023
DOI: 10.3390/cells12151940
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Viable Circulating Tumor Cells from Triple-Negative Breast Cancer Patients Using TetherChip Technology

Abstract: Metastasis, rather than the growth of the primary tumor, accounts for approximately 90% of breast cancer patient deaths. Microtentacles (McTNs) formation represents an important mechanism of metastasis. Triple-negative breast cancer (TNBC) is the most aggressive subtype with limited targeted therapies. The present study aimed to isolate viable circulating tumor cells (CTCs) and functionally analyze them in response to drug treatment. CTCs from 20 TNBC patients were isolated and maintained in culture for 5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…VRB also induced autophagocytosis and reduced the scratch-healing rate effectively in all cell lines, while further demonstrating variable efficacy across the NSCLC cells. The results here are in line with previous results from our lab and literature [51][52][53]. VRB has been well documented to produce variable effects in cancer therapy, owing to both, the type of tumor and its respective genetic profile, and the administration pattern of the drug [54][55][56].…”
Section: Discussionsupporting
confidence: 92%
“…VRB also induced autophagocytosis and reduced the scratch-healing rate effectively in all cell lines, while further demonstrating variable efficacy across the NSCLC cells. The results here are in line with previous results from our lab and literature [51][52][53]. VRB has been well documented to produce variable effects in cancer therapy, owing to both, the type of tumor and its respective genetic profile, and the administration pattern of the drug [54][55][56].…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that CTCs may have a great predictive value in detecting activating mutations, such as epidermal growth factor receptor (EGFR) and EML4-ALK fusion protein, that may be superior to ctDNA analysis [28,29]. We have also shown that live CTCs can be used for functional analysis and evaluation of drug efficacy using TetherChip technology [30].…”
Section: Discussionmentioning
confidence: 99%
“…10 Unfortunately, the generation of heterogeneous CTCs occurs when cancer cells undergo epithelial-to-mesenchymal transition (EMT) during migration, which seriously compromises the accurate detection of CTCs. 11,12 Previous researches have shown that EMT is fairly common in tumors and plays an important role in tumor metastasis, making tumor cells more aggressive, drug-resistant, and metastasizing. 13,14 Therefore, it is very meaningful and urgent to establish efficient detection methods to address the challenge of heterogeneous CTCs.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) are tumor cells that spontaneously circulate in the peripheral blood after separating from primary or metastatic tumors. Efficient enrichment and analysis of CTCs can facilitate real-time tumor dynamics monitoring, therapeutic effect evaluation, and real-time individual treatment implementation. , Various methods have been developed to detect CTCs, such as microfluidic chips, immunomagnetic beads, polymerase chain reactions, and immunofluorescence staining . Unfortunately, the generation of heterogeneous CTCs occurs when cancer cells undergo epithelial-to-mesenchymal transition (EMT) during migration, which seriously compromises the accurate detection of CTCs. , Previous researches have shown that EMT is fairly common in tumors and plays an important role in tumor metastasis, making tumor cells more aggressive, drug-resistant, and metastasizing. , Therefore, it is very meaningful and urgent to establish efficient detection methods to address the challenge of heterogeneous CTCs.…”
Section: Introductionmentioning
confidence: 99%